Extent of misclassification of death from Creutzfeldt-Jakob disease in England 1979-96: retrospective examination of clinical records. Issue 7228 (15th January 2000) - Majeed, Azeem; Lehmann, Petra; Kirby, Liz; Knight, Richard; Coleman, Michel
Abstract: Objective: To investigate the extent to which deaths from Creutzfeldt-Jakob disease were misclassified during 1979-96. Design: Structured review of clinical records based on predetermined criteria to determine whether death could have been due to sporadic or variant Creutzfeldt-Jakob disease. Setting: 100 health authorities and 275 NHS trusts in England. Subjects: 1485 people who died aged 15-44 years from selected neurological disorders in England during 1979-96. Main outcome measure: Cause of death. Results: The clinical records of 705 (48%) subjects were successfully traced. Tracing of clinical records was highest in subjects who died during 1990-6. There was sufficient information in the records of 640 (91%) of the 705 subjects to exclude Creutzfeldt-Jakob disease as a cause of death. In 61 (9%) subjects, there was insufficient information to reach any conclusion about the validity of the cause of death recorded on the death certificate. The clinical records of four subjects were examined further by the National Creutzfeldt-Jakob Disease Surveillance Unit; none was thought to have died from Creutzfeldt-Jakob disease. Conclusions: No new cases of sporadic or variant Creutzfeldt-Jakob disease were detected in a sample of deaths most likely to have included misclassified cases. This suggests that the surveillance system is unlikely to have missed a significant number of cases among people aged 15-44 years. Hence, any rapid increase in the number of cases of variant Creutzfeldt-Jakob disease in this age group is likely to be real not artefactual.